Anthropometric and physiological characteristics of junior Japanese elite male basketball players - Ohya, T.; Hakamada, N.; Inaba, Y. (Japanese Journal of Elite Sports Support, 2010)
The Japanese men`s national basketball team last participated in the Montreal Olympic Games in 1976. Improving basketball players` performance and training young basketball players are both necessary to ensure Japan`s participation in future Olympics. An understanding of the anthropometric and physical fitness characteristics of elite basketball players is needed to develop training programs and guide talent identification. The aim of this study was to understand the anthropometric and physiological characteristics of junior Japanese elite male basketball players.For this, we used anthropometric and physical fitness measurements to compare junior Japanese elite male basketball players with senior Japanese elite basketball players. Thirteen junior Japanese elite male basketball players (age 15.6 ± 0.5 years) and ten senior Japanese elite male basketball players (age 24.7 ± 2.6 years) were measured for body size and weight, aerobic fitness, lower body muscular power, and leg muscle strength. We found that body weight (76.0 ± 8.0 vs. 92.3 ± 14.6 kg) and lean body weight (67.7 ± 5.7 vs. 79.7 ± 12.3 kg) greatly differently between junior and senior players, respectively. Meanwhile, standing height (186.3± 8.7 vs.191.6± 11.1cm), VO2peak(58.8± 3.9 vs. 55.4± 5.7mL x kg-1 x min-1), counter movement jump height, and maximal knee extension and flexion torques at angular velocities of 60° x s-1and180°?s-1 were not significantly different between the groups, respectively. Coaches and national federation can compare our data with data from other national and international elite male basketball players to determine individual weaknesses, design training programs and guide talent identification.